TINJAUAN KESULITAN GURU BIOLOGI DALAM MELAKSANAKAN PENILAIAN BERBASIS KELAS DI SMA NEGERI SE KOTA BUKITTINGGI - Erlan Sari, Revy; Risdawati, M.Si., Renny; Maizeli, Annika (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ The assessment based on the class developed to give encouragement for teacher. To teach more systematic and aimed, but teacher still have difficulty in doing assessment based on the class. This because of decrease information about assessment based on the class that teacher gets. The assessment have purposed to know the level of troubles that biology teacher class XIÂ Â SMA at Bukittinggi faced in implementation of assessment based on the class and also to know whatâs the difficulty which biology teacher class XI SMA at Bukittinggi encountered for doing assessment based on the class. A kind of this research is descriptive. In this research have 6 samples of biology teacher class XI who scattered from 5 schools for SMA at Bukittinggi in 2014. This research do a validity of questionnaire test biology teacher in implementation of assessment based on the class gets a valid output. The result of this research is the difficulty that biology teacher class XI SMA at Bukittinggi fronting have realization output 83,15% include in less difficult, and the level of difficult about 16,85%. In totally, the assessment based on the class that doing be able to find a result for assessment written test as not difficult category.Â